ATTITUDE TOWARDS WOMEN IN THE UZBEKISTAN SSR AND FIRST FEMALE HISTORIANS - Tangirova Nigora Abdugani kizi (Scholar Express Journal, 2024)
This article analyzes the attitude towards women in the Uzbekistan SSR, as well as the life and scientific activity of early female historians.
Keywords: Uzbekistan SSR; Soviet policy; academy; science